Revised Estimates of the Impact of Climate Change on Extreme Poverty by 2030 - Jafino, Bramka Arga; Walsh, Brian; Rozenberg, Julie; Hallegatte, Stephane (World Bank, Washington, DC, 2020)
Thousands of scenarios are used to provide updated estimates for the impacts of climate change on extreme poverty in 2030. The range of the number of people falling into poverty due to climate change is between 32 million and 132 million in most scenarios. These results are commensurate with available estimates for the global poverty increase due to COVID-19. Socioeconomic drivers play a major role: optimistic baseline scenarios (rapid and inclusive growth with universal access to basic services in 2030) halve poverty impacts compared with the pessimistic baselines. Health impacts (malaria, diarrhea, and stunting) and the effect of food prices are responsible for most of the impact. The effect of food prices is the most important factor in Sub-Saharan Africa, while health effects, natural disasters, and food prices are all important in South Asia. These results suggest that accelerated action to boost resilience is urgent, and the COVID-19 recovery packages offer opportunities to do so.